Catalytic properties of Thallium-containing mesoporous silicas - A. Baradji; K. Bachari; J. Amari (Arabian Journal of Chemistry, 2017)
The benzylation of benzene by benzyl chloride over a series of Thallium-containing mesoporous silicas with different Tl contents has been investigated. These materials (Tl-HMS-n) have been characterized by chemical analysis, N2 adsorption/desorption isotherm and X-ray diffraction (XRD). The mesoporous Thallium-containing materials showed both high activity and high selectivity for the benzylation of benzene. More interesting is the observation that these catalysts are always active and selective for large molecules like naphthenic compounds such as methoxynaphthalene.